Paganism and the World Forum of Religions - York, Michael (Journal of the Irish Society for the Academic Study of Religions, 2016)
Using the sociological tool known as the ideal-type, there is a distinction to be made for ancient, indigenous and contemporary paganisms vis- à-vis the more established world such as Christianity, Islam, Hinduism, Buddhism, etc. While both the New Age movement and contemporary Western paganism may be understood through what Gerlach and Hine identified as the segmented-polycentric-integrated-network (SPIN), New Age may be increasingly understood as one more denomination under the rubric of paganism. In general, pagan religiosity is to be identified through its corpo-spirituality, veneration of nature, this-worldly focus, plural understanding of the divine, humanistic undercurrent and pursuits of enchantment and pleasure. Diverging from the characteristics of the pagan ideal-type as well as deep, generic and/or vernacular paganisms are both gnostic and secular forms of paganism. The multiplicity of religions, however, allows and encourages the internal dialogue of paganism with itself as the external conversation with the other religions of the world.